Short-term comprehensive cardiac rehabilitation after AMI is associated with reduced 1-year mortality: results from the OMEGA study: - Rauch, Bernhard; Riemer, Thomas; Schwaab, Bernhard; Schneider, Steffen; Diller, Frank; Gohlke, Helmut; Schiele, Rudolf; Katus, Hugo; Gitt, Anselm; Senges, Jochen (European journal of preventive cardiology, 2014)
Background The prognostic effect of early, comprehensive short-term cardiac rehabilitation on top of current, guideline-adjusted treatment of acute myocardial i...